The obscured nucleus and shocked environment of VV 114E revealed by JWST/MIRI spectroscopy. Issue 3 (20th December 2022) - Donnan, F R; García-Bernete, I; Rigopoulou, D; Pereira-Santaella, M; Alonso-Herrero, A; Roche, P F; Hernán-Caballero, A; Spoon, H W W
ABSTRACT: Compact Obscured Nuclei (CONs) potentially hide extreme supermassive black hole (SMBH) growth behind large column densities of gas/dust. We present a spectroscopic analysis of the heavily obscured nucleus and the surrounding environment of the eastern region of the nearby ( z = 0.02007) interacting galaxy VV 114 with the JWST Mid-InfraRed Instrument (MIRI). We model the spectrum from 4.9 to 28 μ m to extract polycyclic aromatic hydrocarbon (PAH) emission and the underlying obscured continuum. We find that the NE nucleus (A) is highly obscured where the low PAH equivalent width (EW) ratio, EW(12.7)/EW(11.3), reveals a dust enshrouded continuum source. This is confirmed by decomposing the continuum into nuclear and star-forming where the nuclear component is found to be typical of CONs. The 11.3/6.2 PAH flux ratio is consistent with originating in star-forming regions rather than typical AGN. The second nucleus (B) is much less obscured, with PAH flux ratios also typical of star-forming regions. We do not detect any high ionization lines such as [Ne v ] or [Ne vi ] which suggests that if an AGN is present it must be highly obscured. Additionally, we detect a shock front south of the secondary nucleus (B) in the [Fe ii ] (5.34 μ m) line and in warm molecular hydrogen. The 6.2 PAH emission does not spatially coincide with the low-J transitions of H2 but rather appears strong at the shock front which may suggest destruction of the ionized PAHs in the post-shock gas behind the shock front.